Towards Urban Frameworks: Accommodating Change in Urban Cultural Landscapes - (:unkn) unknown (My University, 1995)
This project is based upon a case study of an existing urban environment in New York City. The history of this environment has been characterized by a succession of ethnic communities and the consequent creation of their distinct cultural landscapes. This suggests that important insights can be gleaned which are generalizable to the practice of urban design. These insights involve the creation of urban environments that are designed to accommodate change in cultural landscapes. In designing for such change, it is argued, new environments would be more likely to resist obsolescence.